Revolutionizing anti-cancer drug discovery against breast cancer and lung cancer by modification of natural genistein: an advanced computational and drug design approach - Akash, Shopnil; Bibi, Shabana; Biswas, Partha; Mukerjee, Nobendu; Khan, Dhrubo Ahmed; Hasan, Md. Nazmul; Sultana, Nazneen Ahmeda; Hosen, Md. Eram; Jardan, Yousef A. Bin; Nafidi, Hiba-Allah; Bourhia, Mohammed (Frontiers in Oncology, 2023)
Firstly, the Pass prediction spectrum was analyzed, revealing that the designed Genistein analogs exhibit improved antineoplastic activity. In the prediction data, breast and lung cancer were selected as primary targets. Subsequently, other computational investigations were gradually conducted. The molecular docking scores ranged from -11.0 to -10.0 kcal/mol against the target protein (PDB ID: 3HB5), while -7.2 kcal/mol to -9.5 kcal/mol was reported against the lung cancer targeted receptor. The mentioned compounds have shown acceptable results for in silico ADME, AMES toxicity, and hepatotoxicity estimations, which are fundamental for their oral medication.It is noteworthy that the initial binding affinity was only -8.7 kcal/mol against the breast cancer targeted protein (PDB ID: 3HB5). However, after the modification of the functional group, when calculating the binding affinities, it becomes apparent that the binding affinities increase gradually, reaching a maximum of -11.0 and -10.0 kcal/mol. Similarly, the initial binding affinity was only -8.0 kcal/mol against Lung cancer (PDB ID: 2P85), but after the addition of binding affinity, it reached -9.5 kcal/mol. Finally, a molecular dynamics simulation was conducted to study the molecular models over 100 nanoseconds and examine the stability of the docked complexes. The results indicate that the selected complexes remain highly stable throughout the 100 ns molecular dynamics simulation runs, displaying strong correlations with the binding of targeted ligands within the active site of the selected protein. Now, it is time to proceed to clinical or wet lab experiments to determine the practical value of the proposed compounds.